PARMENIDES IN ``BOUNDARIES OF NARRATIVE'' - Forgac, Marcel (Bohemica Olomucensia, 2022)
The paper is a commentary formulated as a reflection on the argumentative sequence established by Gerard Genette in his study Boundaries of Narrative. Genette mentions Parmenides as one of the writers excluded from Aristotle's ``Poetics'' because they ignore the representational function of poetry. The aim of the paper is to recapitulate the general poetic background of Parmenides' epic poem and then to verify how valid is Genette's inclusion of Parmenides among the writers of direct expression.
Keywords: Genette; Parmenides; narrative; philosophy; Aristotle